Regional dynamics of economic performance in the EU: To what extent spatial spillovers matter? - Selin Ozyurt; Stephane Dees (European Regional Science Association (ERSA), 2015)
This paper investigates the main determinants of economic growth in the European Union from a regional perspective. The analysis is based on a recently available dataset from the European Cluster Observatory covering 253 European regions over the period 2002-2008. In addition to the traditional determinants of regional growth (such as investment, human capital developments, innovation and infrastructure endowment), the growth analysis accounts for spatial effects related to the existence of externalities from neighbouring regions. The spatial Durbin fixed-effect panel specification captures spatial feedback effects from the neighbours through spatially lagged dependent and independent variables. Social-economic environment and traditional determinants of growth are found to be significant. In particular, investment, infrastructure and human capital endowment, accessibility and innovation capacity explain both growth dynamics and cross regional differences. We do not find evidence of convergence among regions over the study period. By contrast, we detect a regional cluster in the core of Europe specialised in activities with high growth potential. Our findings confirm the significance of spatial spillovers. Specifically, business investment and skilled workforce migration have a positive ? direct and indirect ? impact on economic growth of the European regions.
Keywords: O17; O31; O18; R12; 330; Spatial Durbin Panel Models; Economic Growth; Cluster Analysis; European Union